Reforming the Christian faith theological interpretation after the Protestant reformation - Karlberg, Mark W. (Eugene, OR : Wipf & Stock, 2017)
Central to the mission of the church with each passing generation is the elucidation of the gospel of Christ, which is the heart of the Christian message. Witness to God's saving word in Scripture comes in response to discussions and debates arising over the course of church history. Our study highlights some of the unity and disunity found within the Reformed tradition, Reformation and modern. Beginning with the subject of the development of doctrine over the course of church history, we take up the foundational issue of biblical hermeneutics (the question of how we are to interpret the Bible.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 16, 2018).
Master record variable field(s) change: 050, 072, 082, 610, 650
Keywords: Westminster Theological Seminary (Philadelphia, Pa.); Orthodox Presbyterian Church -- Controversial literature; Reformation -- Anniversaries, etc; Protestantism -- History of doctrines; Covenant theology; Justification (Christian theology); RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books